A Comparison of Self-Reported Sexual Risk Behaviors between U.S. Civilian and Active Duty Military Women - Stahlman, Shauna (Sex Health, 2015)
Women in the military report a high prevalence of sexual risk behaviors, such as binge drinking and new or multiple sexual partnerships. However, demographical differences pose challenges to making comparisons with civilians. We used two public-use datasets to compare prevalence of sexual risk behaviors between sexually active military and civilian women, after adjusting for demographic factors. We found that women in the military reported a higher prevalence of binge drinking and new/multiple sexual partners as compared with civilians, which suggests that military women are truly a high-risk group and the military environment may at least partially facilitate these risk behaviors.